Factores relacionados a la no adherencia al targa en adultos con VIH/SIDA atendidos en IPRESS I- 4, Requena2019 - Garcia Ramirez, Veronica Janet (2023)
The objective of the research was to determine the relationship between sociodemographic factors: age, sex, time of illness, level of education and origin; and non-adherence to ART in adults with HIV/AIDS who attend the Health Services Provider Institution I-4 Requena, in 2019. Methodology: the observational method was used, the type of design was descriptive, correlational and retrospective. The study population consisted of 84 patients. The instrument used was the questionnaire, made up of two sections, in the first section 5 items related to sociodemographic factors were considered and the second section consisted of 11 items related to nonadherence. The time required for its application was 10 minutes, it had a validity of 96.9% and a reliability of 0.811. The results indicate that of 84 patients, 97.6% (82) patients presented low non-adherence to treatment, 69.0% (58) were young adults. Likewise, 97.6% (82) patients presented low non-adherence to treatment, 84.5% (71) had more than 1 year of the disease. To establish a relationship, the statistical test of the Contingency Coefficient was used...indicating that there is a statistically significant relationship with the level of education with CC =0.261 and p=0.046, there being no relationship with age with CC=0.098 and p=0.845; sex CC=0.195 and p=0.068; ART time CC=0.067 Y P=0.829 and origin CC=0.087 and p=0.424. The study concludes that the higher degree of instruction the study subject has, the lower the degree of non-adherence.